Associations Between Parental Health Literacy, Use of Asthma Management Plans, and Child's Asthma Control. (February 2016) - Brigham, Erin L.; Goldenberg, Larry; Stolfi, Adrienne; Mueller, Gary A.; Forbis, Shalini G.
Background . There are some studies demonstrating the effectiveness of the provision of written asthma action plans in improving asthma outcomes. There exist little data on the ability of parents to use these plans to make asthma care decisions. Objective . To assess the associations between parental health literacy (HL), parental ability to use a written asthma management plan (WAMP), and child's asthma control. Methods . Parents completed a survey with questions related to WAMPs and child's asthma, a HL screening tool, and 5 asthma vignettes. For vignettes, parents identified asthma control zone and then made decisions about asthma management. WAMP scores were totaled (0-32) and converted to a percent correct score. Associations between parental HL, WAMP scores, child's asthma control, and demographics were determined with independent t tests or 1-way analysis of variance, and chi-square tests. Variables significantly associated with WAMP scores or asthma control were included in multiple logistic regression or multiple linear regression analyses. Results . A total of 176 surveys were included; the mean ± SD WAMP score was 58.9% ± 22.2%, and 25% of respondents had limited HL. Of respondents' children, 38% had not well/poorly controlled asthma. In multiple regression analysis controlling for education level, limited HL was significantly associated with WAMP score ( b = 11.3, standard error 3.8, P = .004). WAMP score was not associated with asthma control. Limited HL was associated with poor asthma control in univariate analysis, but not in a logistic regression model controlling for other significant variables. Only unmarried marital status (adjusted odds ratio 4.4, 95% CI 1.8-10.8, P = .001) was associated with asthma control. Conclusion . HL is associated with parental ability to use WAMPs to respond to asthma scenarios. Parental HL may play a role in parents' ability to appropriately use WAMPs.